A framework for synergy evaluation and development in heavy industries - Mohammed, Feisal; Yao, Hong; Tade, Moses; Biswas, Wahidul (Springer Singapore, 2013)
Industrial ecology research has so far assessed the economic and environmental implications of existing synergies. However, it warrants investigations into unused by-products, which can potentially generate resource synergies between neighbouring industries and thus help to attain the zero wastes scenario. This paper presents a theoretical framework for sustainability assessment to aid new by-product synergies evaluation in the Kwinana Industrial Area of Western Australia. Accordingly, a generic symbiotic relation is suggested to link various industries together as a first step of the framework. Secondly, the principle of process engineering has been applied for the identification and development of resource synergies. Thirdly, the feasibility analysis of green processing is presented using a case study.